DAMPAK PERKEMBANGAN PERKEBUNAN KELAPA SAWIT TERHADAP HARAPAN PENDIDIKAN ANAK DI DESA LABOY JAYA - Rezki Yana; Henny Indrawati; Hendripides Hendripides (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The research aims to determine the impact of oil palm plantation developments on the hope of children's education in the village Bangkinang District Jaya. The population in this study of 204 farmers and in this research the sampling used is Purposive Sampling technique with a total of 65 people. To determine the number of samples using criteria is to have school-age children. The data collection techniques used are questionnaires distributed to respondents. Analysis of data using descriptive and crosstab analysis. The results of the research in Laboy village found the hope of child education in the high category. The development of oil palm plantations positively impacts the children's education in the village of Bangkinang District Jaya. While the results of research on land area less than 2 hectares have a high expectation for the education of children.Key Words: Development of Oil Palm Plantations, Children Education Expectations.